2020
DOI: 10.3389/fpsyg.2020.536510
|View full text |Cite
|
Sign up to set email alerts
|

Biomarking Trait Resilience With Salivary Cortisol in Chinese Undergraduates

Abstract: This study aimed to examine the relationship between trait resilience and salivary cortisol in a group of Chinese undergraduates. The Chinese versions of the Brief Resilience Scale and a measure of optimism, the revised Life Orientation Test were administered to 49 Chinese undergraduates who provided self-collected saliva samples six times per day (immediately after waking; 0.5, 3, 6, and 12 h thereafter; and at bedtime) over 3 consecutive weekdays. The cortisol data were aggregated across the 3 days to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Basal morning serum cortisol levels were also found to be positively associated with resilience in the study conducted by Farina et al (2019) with active‐duty army soldiers, with higher morning cortisol concentrations being observed among more resilient subjects. Similar findings were reported by Lai et al (2020), who observed a positive (although not significant) correlation between resilience and cortisol area under the curve with respect to the ground (AUCg) response in a group of undergraduate students.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Basal morning serum cortisol levels were also found to be positively associated with resilience in the study conducted by Farina et al (2019) with active‐duty army soldiers, with higher morning cortisol concentrations being observed among more resilient subjects. Similar findings were reported by Lai et al (2020), who observed a positive (although not significant) correlation between resilience and cortisol area under the curve with respect to the ground (AUCg) response in a group of undergraduate students.…”
Section: Resultssupporting
confidence: 90%
“…Lai et al, 2020 found both a stronger CAR and a steeper diurnal cortisol slopes (DS) among undergraduate students with higher levels of resilience. Similarly, O'Connor et al, 2021 observed a positive association between resilience and cortisol awakening response in adults with a history of suicidal ideation or attempt, finding lower levels of the former among those with a weaker total cortisol awakening response.…”
Section: Resultsmentioning
confidence: 99%
“…Here, repetitive stressful experiences can increase the allostatic load, causing HPA axis dysregulation, which in turn may lead to decreased resilience capacity. There are also reports that suggest that high resilience is associated with high AUCi in healthy individuals ( 34 ); such a relationship was also determined in this study ( Figure 4 ). Further studies are needed to evaluate whether an ACE individual with low resilience recovers CAR by enhancing resilience through psychosocial interventions, such as MBT.…”
Section: Discussionsupporting
confidence: 88%
“…The HPA axis dysfunction can be assessed by measuring cortisol indicators, such as post-awakening cortisol concentrations (area under the curve with respect to ground, AUCg) or cortisol awakening response (CAR or area under the curve with respect to increase, AUCi). Several studies have reported that high resilience is associated with elevated AUCg or AUCi, and these indices can be considered potential biomarkers ( 34 36 ). Since most resilience evaluations are assessed using a self-reported scale, the addition of an objective biomarker can help achieve a more scientific evaluation of protective factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation